Pemanfaatan Serbuk Besi Sebagai Pengganti Parsial Pasir Dan Silicafume Sebagai Pengganti Semen Terhadap Kuat Tekan Dan Kuat Lentur Beton - Abeng, Christie Bongga; Sariman, Syahrul; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
With the advancement of technology and increasingly complex construction needs, the use of concrete has become essential in infrastructure development. One innovation to improve concrete quality is by adding supplementary or replacement materials. In Indonesia, iron powder is rarely utilized, leading to environmental pollution. This study uses iron powder to partially replace sand, aiming to address waste issues, and incorporates silica fume to partially replace cement. The mixing method replaces sand with 5%, 10%, 15%, 20%, and 25% iron powder and adds 10% silica fume relative to the cement amount in each iron powder variation. Results show that using iron powder and silica fume increases compressive and flexural strength at 5% and 10% iron powder with 10% silica fume. However, iron powder at 15%, 20%, and 25% with 10% silica fume led to reduced strength. Maximum compressive and flexural strength occurred at 10% iron powder with values of 27.55 MPa and 5.07 MPa, indicating that higher iron powder levels reduce compressive and flexural strength.